Serum anti-aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder presenting as acute eosinophilic encephalomyelitis. (February 2018) - Muroishi, Toyoteru; Sakai, Kenji; Yanase, Daisuke; Ikeda, Yoshihisa; Machiya, Tomohiko; Kato-Motozaki, Yuko; Samuraki, Miharu; Yamada, Masahito
Highlights: We report the case of NMOSD presenting as acute eosinophilic encephalomyelitis. Eosinophilia was evident in the cerebrospinal fluid at the early stage. The number of eosinophils in the cerebrospinal fluid decreased subsequently. Abstract: We report the case of a 57-year-old man with neuromyelitis optica spectrum disorder (NMOSD) presenting as acute eosinophilic encephalomyelitis. Magnetic resonance imaging revealed central nervous system lesions typical of NMOSD and anti-aquaporin-4 antibodies in the serum were identified; however, eosinophilia was evident in the cerebrospinal fluid (CSF) at the early stage of the disease. The number of eosinophils in the CSF decreased subsequently. Although activation of eosinophils is known to be an important factor in the development of NMOSD lesions, prominent eosinophilia in the CSF at the early stage of the disease has never been reported in patients with NMOSD.